Evaluation of Fire Resistance of Glass Fibre Concrete in Terms of Various Parameters - Ali Murthada Ali; Musa Hakan Arslan; Mustafa Altın (Doğal Afetler ve Çevre Dergisi)
The mechanical properties of the concrete are improved by adding glass fiber to the fresh concrete mixture. Numerous studies have been carried out in the literature to determine the mechanical properties of glass fiber reinforced concrete (GRC). By adding glass fiber into the concrete, the bending and tensile strength of it increase considerable, and concretes produced in this way are preferred in practice to be thinner. Since there is no comprehensive investigation of the fire performance of the GRC used in practice, this study examined the changes in the mechanical properties of GRC elements subjected to four different (30, 60, 90 and 120 min) fire periods. In the scope of the experimental study, 300 samples including Ø15 / 30 cm cylinder and 4x4x16 cm prism were produced. The effect of glass fiber admixture of 0,5,10,15 and 20 kg / m3 on the compressive and different tensile strength of the concrete was tested on GRC elements exposed to fire for different periods of time. A significant contribution of glass fiber to the tensile strength for unburned samples has been observed, however glass fiber does not contribute to the compressive strength. After 30 minutes of fire, tensile strengths of single and double point bending tests of GRC samples increased. In the case of longer fires, there has not been an increase in this rate.